Increased Virulence in Sunflower Broomrape (Orobanche cumana Wallr.) Populations from Southern Spain Is Associated with Greater Genetic Diversity - Martín-Sanz, Alberto; Malek, Jebri; Fernández-Martínez, José M.; Pérez-Vich, Begoña; Velasco, Leonardo (Frontiers in Plant Science, 2016)
Orobanche cumana Wallr. (sunflower broomrape) is a holoparasitic weed that infects roots of sunflower in large areas of Europe and Asia. Two distant O. cumana gene pools have been identified in Spain, one in Cuenca province in the Centre and another one in the Guadalquivir Valley in the South. Race F has been hypothesized to have arisen by separate mutational events in both gene pools. In the Guadalquivir Valley, race F spread in the middle 1990’s to become predominant and contained so far with race F hybrids. Recently, enhanced virulent populations of O. cumana have been observed in commercial fields parasitizing race F resistant hybrids. From them, we collected four independent populations and conducted virulence and SSR marker-based genetic diversity analysis. Virulence essays confirmed that the four populations studied can parasitize most of the race F resistant hybrids tested, but they cannot parasitize the differential inbred lines DEB-2, carrying resistance to race F and G and, and P-96, resistant to F but susceptible to races G from other countries. Accordingly, the new populations have been classified as race GGV to distinguish them from other races G. Cluster analysis with a set of populations from the two Spanish gene pools and from other areas, mainly Eastern Europe, confirmed that race GGV populations maintain close genetic relatedness with the Guadalquivir Valley gene pool. This suggested that increased virulence was not caused by new introductions from other countries. Genetic diversity parameters revealed that the four populations had much greater genetic diversity than conventional populations of the same area, containing only alleles present in the Guadalquivir Valley and Cuenca gene pools. The results suggested that increased virulence may have resulted from admixture of populations from the Guadalquivir Valley and Cuenca followed by recombination of avirulence genes.